Epidemiology of Salmonella enterica subspecies enterica serotypes, isolated from imported, farmed and feral poultry in the Cayman Islands - Watler, Simon; Toka, Felix N.; Lardé, Hélène; Johnson, Antoinette; Butaye, Patrick (Frontiers in Veterinary Science, 2024)
Non-typhoidal Salmonella (NTS) are common foodborne pathogens throughout the world causing acute gastroenteritis. Compared to North America and Europe, there is little information on NTS in the Caribbean. Here we investigated the prevalence and characteristics of NTS present in the local poultry of the Cayman Islands to determine the public health risk. In total, we collected 156 samples. These were made up of boot swabs of 31 broiler farms and 31 layer farms (62 samples), paper bedding from 45 imported chick boxes, and 49 pooled cecum samples from feral chickens, each sample representing 10 individual chickens. Salmonella was isolated using the ISO 6579 protocol and isolates were characterized using Whole Genome Sequencing (WGS) analysis. Eighteen Salmonella isolates were obtained and comprised six S. enterica subspecies enterica serotypes and one subspecies houtenae serotype. Subspecies enterica serotypes were: S. Kentucky (n = 9), S. Saintpaul (n = 5), S. Javiana (n = 1), S. Senftenberg (n = 1), S. Poona (n = 1) and S. Agona (n = 1). S. Kentucky strains were all ST152 and clonally related to poultry strains from the USA. S. Saintpaul ST50 strains showed clonality to North American strains. Over half of the strains (n=11) contained resistance genes to at least two antibiotic groups and five strains were MDR, mainly those from imported day-old chicks. The blaCMY-2 gene was found in S. Kentucky from day-old chicks. Strains from feral poultry had no acquired AMR genes. In conclusion, our study demonstrates that Salmonella in broilers and layers on the Cayman Islands are often introduced via the importation of day-old chicks. The presence of Salmonella in feral chickens poses a potential risk, since the serotypes are the most commonly isolated from humans in the Cayman Islands. However, due to the strains' low virulence and the absence of antimicrobial resistance (AMR) and plasmids, the overall health risk may be relatively small. Resistance against antibiotics including blaCMY-2 gene, is of public health concern. This may warrant stricter import control measures and highlights the importance of Salmonella surveillance of imported one day old chicks and farmed poultry.